PERANCANGAN ESCAPE HEALING PADA GEDUNG NITOUR DI KAWASAN HARMONI SEBAGAI THIRD PLACE DENGAN PENDEKATAN INFILL - Theana, Biancha; Solikhah, Nafiah (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
One of the icons in the Harmoni area of Central Jakarta is the Nitour Building, which was originally known as the Oger Freres Building in 1810. It served as a tailor shop for glamorous Dutch women's attire before parties at the Societeit De Harmonie building. The strength of Harmoni’s sense of place at that time lay in its role as the center of social and cultural activity in Batavia. The name "Nitour" derived from Netherlands-Indische Touristen Bureau (Dutch Travel Agency), in 1926, and recognized as the first travel agency in Indonesia. Over time, the Nitour Building has declining in  function and significance, as well disconnection from its surrounding environment. While maintaining its remaining colonial architectural character and historical value, the Nitour Building is now being proposed as a Cultural Heritage Building. Changes in the functions of buildings around the Harmoni area have led to a loss of the district’s identity. Based on these findings, a redesign proposal for the Nitour Building is needed, incorporating the concept of a Third Place and Infill Building as a way to restore meaning and identity to the building and its surroundings. The new design of the Nitour Building aims to become a comfortable place for leisure, blending the Third Place concept while preserving the original structure and adding new spaces for workshops. The goal is to revitalize the Harmoni area and position the Nitour Building as a hub for social activity. Keywords:  architecture third place; harmoni area; nitour building; placelessness Abstrak Salah satu ikon di kawasan Harmoni Jakarta Pusat adalah Gedung Nitour yang pada tahun 1810 bernama Gedung Oger Freres sebagai tempat menjahit busana glamor perempuan Belanda sebelum pesta di Gedung Societeit De Harmonie.  Kekuatan place kawasan Harmoni saat itu yaitu menjadi pusat kegiatan sosial dan budaya di Batavia. Nama Nitour diambil dari NetherlandsIndische Touristen Bureau (agen perjalanan Belanda) yang berdiri sejak tahun 1926 dan menjadi agen travel pertama di Indonesia. Dalam perkembangannya, Gedung Nitour mengalami  penurunan fungsi dan peranan serta mengalami diskoneksi dengan lingkungannya. Dengan mempertahankan karakteristik arsitektur kolonial yang masih ada dan nilai sejarah yang dimilikinya, gedung Nitour kini sedang diusulkan untuk dijadikan sebagai Bangunan Cagar Budaya. Perubahan fungsi bangunan di sekitar kawasan Harmoni telah mengakibatkan hilangnya identitas kawasan tersebut. Berdasarkan temuan tersebut, maka diperlukan usulan perancangan ulang Gedung Nitour dengan konsep Third place dan Infill Building sebagai upaya untuk mengembalikan makna dan identitas pada gedung serta kawasannya. Desain baru Gedung Nitour akan menjadi tempat bersantai yang nyaman, menggabungkan konsep Third Place dan mempertahankan bangunan asli dengan penambahan ruang baru untuk workshop. Tujuannya adalah untuk menghidupkan kembali kawasan Harmoni dan menjadikan Gedung Nitour sebagai pusat kegiatan sosial.